Self-reported influence of monetary grants in the choice of a medical residency in remote or under-served areas - Yishay Wasserstrum; Racheli Magnezi; Ofer Tamir; Stav Koren; Dor Lotan; Arnon Afek (BMC, 2019)
Abstract Objectives To evaluate the effect of monetary grants on young physicians' choice of remote or rural hospital-based practice. Background In late 2011, The Israeli Ministry of Health attempted to address a severe physician maldistribution, which involved severe shortages in remotely-located institutions (RLI). The policy intervention included offering monetary grants to residents who chose a residency program in a RLI. Methods A total of 222 residents from various disciplines were recruited; 114 residents from RLI and 108 residents from central-located institutions (CLI), who began their residency during 2012-2014. Participants were surveyed on demographic, academic and professional data, and on considerations in the choice of residency location. Results Residents in RLI attributed significantly more importance to the grant in their decision-making process than did residents from CLI. This effect remained significant in a multivariate model (OR 1.65, 95% CI 1.20-2.27, p = 0.002). The only parameter significantly associated with attributing importance to the grant was older age (OR 1.09, 95% CI 1.00-1.19, p = 0.049). Conclusion The choice of a RLI for residency may be influenced by monetary grants. This is consistent with real-life data showing an increase in medical staffing in these areas during the program's duration. Further studies are needed to determine causality and physical practicality of such programs.